2004
DOI: 10.1097/01.wcb.0000110047.43905.01
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial pO2 in Ischemic Penumbra and Core are Differentially Affected following Transient Focal Cerebral Ischemia in Rats

Abstract: Summary:Stroke causes heterogeneous changes in tissue oxygenation, with a region of decreased blood flow, the penumbra, surrounding a severely damaged ischemic core. Treatment of acute ischemic stroke aims to save this penumbra before its irreversible damage by continued ischemia. However, effective treatment remains elusive due to incomplete understanding of processes leading to penumbral death. While oxygenation is central in ischemic neuronal death, it is unclear exactly what actual changes occur in interst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
149
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(159 citation statements)
references
References 38 publications
(56 reference statements)
9
149
1
Order By: Relevance
“…Aside from improving tissue oxygen delivery to areas of diminished blood flow (Liu et al, 2004), it has been suggested that oxygen may partially be neuroprotective by inducing cerebral vasoconstriction in normal brain tissue, with subsequent decreases in intracranial pressure and/or an inverse steal of blood into the mismatch area (Nighoghossian and Trouillas, 1997). However, no significant changes in CBF were observed in this study, corroborating previous studies that showed unchanged cerebral perfusion during or shortly after oxygen treatment in models of focal cerebral ischemia (Henninger et al, 2006a).…”
Section: Discussionsupporting
confidence: 89%
“…Aside from improving tissue oxygen delivery to areas of diminished blood flow (Liu et al, 2004), it has been suggested that oxygen may partially be neuroprotective by inducing cerebral vasoconstriction in normal brain tissue, with subsequent decreases in intracranial pressure and/or an inverse steal of blood into the mismatch area (Nighoghossian and Trouillas, 1997). However, no significant changes in CBF were observed in this study, corroborating previous studies that showed unchanged cerebral perfusion during or shortly after oxygen treatment in models of focal cerebral ischemia (Henninger et al, 2006a).…”
Section: Discussionsupporting
confidence: 89%
“…[20][21][22][23] Confirmation of 23,31 Of note, although this paper focuses on longitudinal WM changes, it will be of interest to determine differences, if any, between WM compared with graymatter pO 2 in the SHR/SP model using EPR oximetry in future endeavors. We measured pO 2 in the WM of SHR/SP at 6 weeks of age before the onset of severe hypertension; all of the animals in the three groups showed similar levels of pO 2 up to 12 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Electron paramagnetic resonance oximetry measurements obtained at 6 to 8 weeks were consistent with pO 2 values obtained from WKY rats and the literature. [21][22][23] At 9 weeks of age, a gradual increase in WM pO 2 was observed that continued to rise weekly up to 12 weeks of age. At age week 12, a significant 32% increase in pO 2 in the WM of SHR/SP rats was observed compared with baseline measurements at age weeks 6 to 8 as shown in Figure 3A.…”
Section: Long-term Stability and Sensitivity Of Lithium Phthalocyaninementioning
confidence: 96%
See 1 more Smart Citation
“…Our present findings demonstrating reduced hippocampal protein tyrosine nitration and retention of PDHC enzyme activity with normoxic resuscitation support the need for additional preclinical and clinical studies to resolve this issue. The concept that hyperoxia worsens oxidative tissue damage and neurologic outcome after acute brain injury may not, however, apply to other forms of injury, e.g., stroke and trauma, as evidence suggests that hyperoxia can under some circumstances be beneficial [73][74][75][76][77]. The time during which the brain is exposed to high O 2 can also determine whether hyperoxia is helpful or detrimental.…”
Section: Discussionmentioning
confidence: 99%